Tandem Oxidation Activation of Carbon for Enhanced Electrochemical Synthesis of H2O2: Unveiling the Role of Quinone Groups and Their Operando Derivatives - Zhao, Dantong; Jiao, Dongxu; Yi, Lingya; Yu, Yang; Zou, Jiajia; Cui, Xiaoqiang; Hu, Weihua (Small (Weinheim an der Bergstrasse, Germany), 2024)
Oxygen‐doped carbon materials show great promise to catalyze two‐electron oxygen reduction reaction (2e‐ORR) for electrochemical synthesis of hydrogen peroxide (H2O2), but the identification of the active sites is the subject of ongoing debate. In this study, a tandem oxidation strategy is developed to activate carbon black for achieving highly efficient electrochemical synthesis of H2O2. Acetylene black (AB) is processed with O2 plasma and subsequent electrochemical oxidation, resulting in a remarkable selectivity of >96% over a wide potential range, and a record‐setting high yield of >10 mol gcat−1 h−1 with good durability in gas diffusion electrode. Comprehensive characterizations and calculations revealed that the presence of abundant C═O groups at the edge sites positively correlated to and accounted for the excellent 2e‐ORR performance. Notably, the edge hydroquinone group formed from quinone under operando conditions, which is overlooked in previous research, is identified as the most active catalytic site. A tandem oxidation strategy is developed to activate carbon black for achieving highly efficient electro‐synthesis of H2O2 with a remarkable selectivity of >96%, a yield of >10 mol gcat−1 h−1 and good durability in gas diffusion electrode. Notably, the edge hydroquinone group formed from quinone under operando conditions, which is overlooked in previous research, is identified as the most active catalytic site for 2e‐ORR.